2016
DOI: 10.18632/oncotarget.12555
|View full text |Cite
|
Sign up to set email alerts
|

MEK1 is required for the development of NRAS-driven leukemia

Abstract: The dual-specificity kinases MEK1 and MEK2 act downstream of RAS/RAF to induce ERK activation, which is generally considered protumorigenic. Activating MEK mutations have not been discovered in leukemia, in which pathway activation is caused by mutations in upstream components such as RAS or Flt3. The anti-leukemic potential of MEK inhibitors is being tested in clinical trials; however, downregulation of MEK1 promotes Eμ-Myc-driven lymphomagenesis and MEK1 ablation induces myeloproliferative disease in mice, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…It is tempting to speculate that, in the latter subset, the strict feedback control of PI3K signaling regulates proliferation, preserving a pool of self-renewing clones, whereas in fast-proliferating HSC pools, reduced feedback control would tilt the balance toward sustained PIP 3 signaling, fast proliferation, and ultimately exhaustion. In line with this hypothesis, MEK1 ablation or inhibition restricts NRAS-driven disease ( Nowacka et al., 2016 , Wang et al., 2013 ) and mTOR activation suppresses leukaemogenesis in PTEN-deficient animals ( Kalaitzidis et al., 2012 , Lee et al., 2010 ); targeting MEK/ERK to modulate both pathways could promote the exit of malignant stem cells from quiescence to sensitize them to chemotherapy and/or stimulate their differentiation.…”
Section: Discussionmentioning
confidence: 85%
“…It is tempting to speculate that, in the latter subset, the strict feedback control of PI3K signaling regulates proliferation, preserving a pool of self-renewing clones, whereas in fast-proliferating HSC pools, reduced feedback control would tilt the balance toward sustained PIP 3 signaling, fast proliferation, and ultimately exhaustion. In line with this hypothesis, MEK1 ablation or inhibition restricts NRAS-driven disease ( Nowacka et al., 2016 , Wang et al., 2013 ) and mTOR activation suppresses leukaemogenesis in PTEN-deficient animals ( Kalaitzidis et al., 2012 , Lee et al., 2010 ); targeting MEK/ERK to modulate both pathways could promote the exit of malignant stem cells from quiescence to sensitize them to chemotherapy and/or stimulate their differentiation.…”
Section: Discussionmentioning
confidence: 85%
“…The authors found that THP1 ( NRAS mutated— KMT2A rearranged) showed greater sensitivity to MEK inhibitors than HL60 and OCI‐AML3 ( NRAS mutated—non‐ KMT2A rearranged) and RAS wild‐type non‐ KMT2A ‐rearranged AML cell lines. By contrast, neither knockdown nor knockout of MEK1 affected the proliferation of THP1 105 . These results might suggest that simultaneous targeting of MEK1 and MEK2 might be fundamental to achieve a therapeutic effect.…”
Section: Targeting the Ras Pathway In Kmt2a‐driven Leukemiamentioning
confidence: 90%
“…By contrast, neither knockdown nor knockout of MEK1 affected the proliferation of THP1. 105 These results might suggest that simultaneous targeting of MEK1 and MEK2 might be fundamental to achieve a therapeutic effect.…”
Section: The Impact Of Subclonal Mutations On Kmt2adriven Leukemogenesismentioning
confidence: 99%
“…Moreover, MEK1 phosphorylation by activated ERK provides a feedback mechanism to counterbalance AKT/ mTORC1 activation, presenting HSCs with the rate-limiting feedback mechanism that controls their fitness and re-entry into quiescence (Figure 2) (98). In myeloid leukemogenesis, oncogenic NRAS G12D activates both MAPK and PI3K signaling, and can promote the expansion of pre-leukemic clones in some contexts (99)(100)(101)(102). It is interesting to consider that disruption of this feedback loop that controls the duration of PI3K signaling and the production of PIP3could exhaust the pool of fast-proliferating HSCs induced by chemotherapy, while at the same time this could benefit the expansion of a pool of selfrenewing pre-leukemic clones.…”
Section: Integration Of Pi3k/akt With the Mapk Pathway In Hscs And Lscsmentioning
confidence: 99%